The phenetic relationship of citrus plants based on the morphological and anatomical characteristics - MOHAMAD NURZAMAN; TIA SETIAWATI; RUSDI HASAN; NAZLA KARUNIA QOTRUNNADA; JOKO KUSMORO; NANDANG PERMADI; EUIS JULAEHA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nurzaman M, Setiawati T, Hasan R, Qotrunnada NK, Kusmoro J, Permadi N, Julaeha E. 2024. The phenetic relationship of citrus plants based on the morphological and anatomical characteristics. Biodiversitas 25: 1201-1213. Indonesia stands as a global biodiversity hub, boasting an exceptional richness that earns it the distinction of being a mega-biodiversity country. Among its diverse ecosystems, the Rutaceae family holds significance, encompassing numerous genera, notably the Citrus genus, which showcases a splendid array of citrus plants. This research aimed to determine phenetic relationships based on the morphological and anatomical characters of seven citrus plants (Citrus reticulata var. Chokun, C. reticulata var. Fremont, C. reticulata var. Santang, C. reticulata var. Dekopon, C. aurantium var. variegata, C. aurantium, and C. limon) in Parongpong District, West Bandung Regency, West Java. The method used in this research was explorative with purposive sampling. This study collected three samples for respective citrus plants for character observations of leaf morphology, anatomy, and fruit morphology. Morphology and anatomy observations were conducted in the Department of Biology, Padjadjaran University laboratory. The description of morphological and anatomical data obtained from each orange plant was then analyzed using NTSYS PC version 2.11a software to obtain similarity values using the dendrogram analysis method. Phenetic analysis of seven orange plants produced a dendrogram divided into 2 main branches, branch I and branch II, with a similarity coefficient of 0.3846. Branch I consists of Chokun orange (Citrus reticulata var. Chokun), Fremont orange (C. reticulata cv. Fremont), Santang orange (C. reticulata cv. Santang), and variegated orange (C. sinensis cv. variegata) and branch II consists of dekopon orange (C. reticulata var. Dekopon), Sunkist orange (C. aurantium), and lemon (C. limon).